(untitled) (Pedagogical Horizons, 2024)
Currently, 51,000 children affected by poverty between the ages of 0 and 4 attend an elementary educational institution (Statistik Austria, 2023, p. 108) and this raises the question of how families affected by poverty can be supported in elementary educational institutions through poverty-sensitive family education. In their day-to-day work, early childhood education professionals are confronted with the effects of poverty on children and their families and, in addition to a professional pedagogical attitude, also need knowledge about the current poverty situation in society. Family education focuses on the holistic education of families, taking particular account of their respective living environment and living conditions (Fischer, 2021, p. 53). Elementary educational institutions with good pedagogical quality standards can help to compensate for the consequences of poverty and form a valuable protective factor for children in poverty (Albers, 2015, p. 18; David & Klein, 2024, p. 88; Keßel, 2020, p. 62; Weigelt, 2011, p. 5). However, poverty prevention is an issue that must be addressed structurally at a political level and represents a social obligation. Elementary educational institutions can have a limited impact here, but "poverty sensitivity must be a pedagogical requirement" (Keßel, 2020, p. 62).